Cryptographic agility and interoperability : proceedings of a workshop - Johnson, Anne Frances (Cyber resilience workshop series., 2017)
"In May 2016, the National Academies of Sciences, Engineering, and Medicine hosted a workshop on Cryptographic Agility and Interoperability. Speakers at the workshop discussed the history and practice of cryptography, its current challenges, and its future possibilities. This publication summarizes the presentations and discussions from the workshop"--Publisher's description